Performance of dynamic anaerobic membrane bioreactor DAnMBR with phase separation in treating high strength food processing wastewater - Mahat, Siti Baizurah; Omar, Rozita; Che Man, Hasfalina; Mohamad Idris, Aida Isma; Mustapa Kamal, Siti Mazlina; Idris, Azni; Chelliapan, Shreeshivadasan; Jamali, Nur Syakina; Abdullah, Luqman Chuah (Elsevier BV, 2021)
Food processing wastewater (FPW) contains high levels of oil and grease (O&G), especially from factories that produce fast food such as nuggets, sausages, and burger patties from beef, poultry, and fish. Therefore, the feasibility of replacing conventional membranes for the treatment of FPW with low-cost dynamic membranes (DM) as an alternative was investigated in this study. An anaerobic DM bioreactor (DAnMBR) was operated for 90 days to evaluate the treatment performance using real FPW under different organic loading rates (OLR) of 3.5, 5.0, 6.5, and 7.0 g COD (chemical oxygen demand)/L day. Once the reactor had reached a steady-state of 90% COD removal, the feed to the reactor was supplemented incrementally with FPW from 10% to 90% as COD to allow the methanogenic bacteria to acclimate any potential inhibitory effects from its recalcitrant content. The bioreactor presented a stable performance at OLR 5.0 g COD/L day with 97.5% removal of COD and reached 20 mg/L total suspended solids (TSS) discharge. A significant correlation between COD fractions removed via acidogenesis and methanogenesis with different OLR was found, indicating that the increase in treatment performance is beneficial to the methanogenic archaea activity. The methane gas production yield achieved a maximum of 0.40 L methane/g CODadded at OLR 3.5 and 5.0 g COD/L day. The average permeate flux in these studies is around 60 L/m2 h. The DM fouled after 57 days (at flux 27.16 L/m2 h immediate drop to 2.16 L/m2 h) when operated at 3.5 g COD/L day. After it fouled, the membrane underwent physical cleaning, backwashed in-situ for 5 min, and reused again without any chemical cleaning. The improved filtration resistance is contributed by the occurrence of DM fouling induced by the soluble microbial products (SMP) and extracellular polymeric substances (EPS) release as well as the increased protein/carbohydrate (P/C) ratio in the mixed liquor.